Formulation of Solid Lipid Nanoparticles Loaded with Nociceptin/Orphanin FQ (N/OFQ) and Characterization in a Murine Model of Airway Hyperresponsiveness - Davida Mirra; Giuseppe Spaziano; Renata Esposito; Debora Santonocito; Rosanna Filosa; Fiorentina Roviezzo; Gaetano Malgieri; Gianluca D'Abrosca; Pasquale Iovino; Luca Gallelli; Roberto Fattorusso; Carmelo Puglia; et al. (MDPI AG, 2022)
Asthma is characterized by chronic inflammation and a variable degree of airway hyperresponsiveness (AHR). Our previous papers documented a role for Nociceptin/Orphanin FQ (N/OFQ) and its receptor N/OFQ peptide (NOP) in AHR. Therefore, the aim of this study was to improve the bioavailability of N/OFQ by developing solid lipid nanoparticles (SLNs). N/OFQ-loaded SLNs were prepared by the Quasi Emulsion Solvent Diffusion (QESD) technique and then characterized. Brown Norway rats were sensitized to ovalbumin (OVA) and treated with an intratracheal administration of saline solution or N/OFQ-SLN. Then, 24 h after the last challenge, functional histological and molecular evaluations were performed. SLNs showed a mean diameter of 233 ± 0.03 nm, a polydispersity index (PDI) value around 0.28 ± 0.02 and a drug release percentage of 84.3. The in vitro release of N/OFQ from SLNs showed that the release of the peptide starts already after two hours of incubation. Animals receiving N/OFQ-SLN showed a significative decrease in allergen-induced AHR compared to the control group. These results showed the positive effects of N/OFQ-SLNs on the inflammatory process and on the mechanical properties of the airways, suggesting that the innovative nanotechnological approach may be therapeutically beneficial for asthmatic patients.